Halogenated flame retardants in tree samples applied as bioindicators for atmospheric pollution. (October 2018) - Dreyer, Annekatrin; Neugebauer, Frank; Rüdel, Heinz; Klein, Roland; Lohmann, Nina; Rauert, Caren; Koschorreck, Jan
Abstract: Coniferous shoots and deciduous tree leaf samples from 10 sites in Germany were taken in 2015 or 2016 within the German Environmental Specimen Bank sampling program and analysed for 24 polybrominated biphenyl ethers (PBDEs) and 19 additional halogenated flame retardants (HFRs). At one site, additional historic samples dating back till 2003 were also investigated. Samples were Soxhlet-extracted, cleaned-up by a non-destructive multi-step procedure involving gel permeation chromatography, and detected by GC-API-MS/MS as well as GC-MS. Besides PBDEs as classical HFRs, emerging HFRs such as Dechlorane Plus, DPTE, DBDPE, or ATE were region-wide observed demonstrating their widespread occurrence in the atmosphere. Highest concentrations in recent samples were found for DBDPE (<230–2760 pg g −1 dry weight (dw)) followed by DPTE (91–1540 pg g −1 dw), BDE209 (<156–461 pg g −1 dw), and BDE47 (<27–505 pg g −1 dw) or DP (31–122 pg g −1 dw). The overall uniform and widespread distribution as well as similar HFR levels and composition profiles observed in recent conifer shoots and corresponding deciduous tree leaves from the same area indicate a prolonged medium to long-range transport as sources. Furthermore, it is demonstrated that both tree types are generally suitable bioindicators for atmospheric pollution with HFRs, although accumulation may vary depending on HFR properties and accumulation period. The historic samples showed decreasing PBDE levels whereas no clear trend could be observed for other investigated HFRs at this site. Highlights: Airborne flame retardants were measured in coniferous shoots and deciduous tree leaves. Both tree types are generally suitable bioindicators of atmospheric flame retardants. Chlorinated and brominated flame retardants are widely distributed in German tree samples. Emerging flame retardants are more prevalent than PBDEs.